Hidrograf Satuan Sintetik Limantara (Studi Kasus di Sebagian DAS di Indonesia) - Lily Montarcih Limantara (Rekayasa Sipil, 2009)
Ideally, every watershed has its own particular unit hydrograph. If the physical and hydrologicalconditions in general are quite homogeneous, it would be quite possible to create a new SUH model thatresembles the ones made up by previous researchers. The SUH model is intended purposefully for (1)finding out the nature of watershed responses against precipitation data input, where by it could become thesupportive warning systems to areas that are vulnerable to flooding, (2) resuming up hydrograph dataavailability that are previously vacant due to the operational problem of the Automatic Water Level Recorder(AWLR), and (3) producing a specific SUH model for Indonesia (SUH Limantara) with a simplemathematical model and without the necessary parametric calibration prior of its application.This research was done on Java island (involving 6 watersheds and 67 sub-watersheds), on Bali island(involving 2 watersheds and 13 sub-watersheds) and on the east part of Borneo island / pulau Kalimantan(involving 1 watershed and 9 sub-watersheds). The watershed criteria are that every watershed has an area of< 5000 km2 and both ARR (Automatic Rainfall Recorder) and AWLR. The calibration model to the observedhydrograph refers to as the amount of the minimum least square. Verification of the result was conducted byfilling up to the model the discrepancies of hydrology data. The results of this study are: the peak time ofhydrograph = 5.773 hours, the recession time of hydrograph = 9,859 hours and the base time of hydrograph =15,632 hours; the peak discharge model: Qp = 0,042 * A0,451 * L0,497 * Lc0,356 * S-0,131 * n0,168; the rising curveequation: Qn = Qp * [(t/Tp)]1,107 and the recession equation: Qt = Qp.e0,175(Tp – t). Based on these results, it isconcluded that: 1) The observed hydrograph really typifies the elongated shaped watershed, which has afaster rising characteristic than that of its recession (hydrograph rising time < hydrograph recession time); 2)There are 5 dominant watershed parameters that influence the peak discharge; they are the length of mainriver/stream (L), followed by the areal size of watershed (A), the length of the main river to be measured upto a point location nearest to the watershed weight centre (Lc), the roughness coefficient (n) and the riverslope (S); 3) the SUH of this research is compared with the observation hydrograph and as a model control.The coefficient of determination (R2) and the level of significance 5% are for the peak discharge (R2 =0,841), the rising curve (R2 = 0,980) and the recession curve (R2 = 0,990). Besides the SUH Limantara isalso compared with the SUH Nakayasu and the deviation obtained is 1,224%.